Physical activity in kidney transplant recipients: benefits, barriers, interventions - Skweres, Martyna; Nieczyporuk, Mateusz; Pucyło, Szymon; Piotrowska, Gabriela; Ceglarz, Katarzyna; Pielaciński, Jan; Rudnik, Aleksander; Sikora, Kinga; Sikora, Aleksandra (Quality in Sport, 2024)
Kidney transplant recipients are reported to have low levels of physical activity compared to the general population. This population is burdened by high prevalence of both traditional and non-traditional cardiovascular risk factors. Physical activity has multiple known health benefits, including reduction of cardiovascular disease risk factors, which are the most common cause of morbidity and mortality in this group. Sedentary lifestyle has been associated with poorer long-term graft outcomes and inferior quality of life. Lack of specific guidelines regarding exercise post-transplantation has been cited as one of the barriers to physical activity, alongside comorbidities and immunosuppressive drugs’ side effects. Exercise interventions, leading to improved physical functioning both pre- and post-transplant, have been demonstrated to lead to improved muscle strength, overall physical functioning, as well as cardiorespiratory performance. Currently available data on physical activity in kidney transplant recipients and its role in long term management of these patients remains limited, but promising results regarding its impact on long-term outcomes highlight the need for further research and development of more precise guidelines and educational programmes for both healthcare professionals and kidney transplant recipients.